2022
DOI: 10.1021/jacs.1c12424
|View full text |Cite|
|
Sign up to set email alerts
|

Modular and Facile Access to Chiral α-Aryl Phosphates via Dual Nickel- and Photoredox-Catalyzed Reductive Cross-Coupling

Abstract: Chiral phosphine-containing skeletons are important motifs in bioactive natural products, pharmaceuticals, chiral catalysts, and ligands. Herein, we report a general and modular platform to access chiral α-aryl phosphorus compounds via a Ni/photoredox-catalyzed enantioconvergent reductive cross-coupling between α-bromophosphates and aryl iodides. This dual catalytic regime exhibited high efficiency and good functional group compacity. A wide variety of substrates bearing a diverse set of functional groups coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 79 publications
1
40
1
1
Order By: Relevance
“…The examination of several ligand scaffolds indicated that common bis­(oxazoline), pyridyloxazoline, and 1,2-diamine ligands ( L1 – L6 ) were ineffective for this enantioselective C­(sp 3 )–H arylation. In contrast, chiral bis­(imidazoline) ligands were found to be exceptionally effective ( L7 – L10 ). We reasoned that the increased electron-donating properties of bis­(imidazoline) ligands may facilitate the challenging oxidative addition of aryl chlorides to the nickel catalyst. Importantly, the nickel chlorides and/or aryl chlorides provide an in situ source of chlorine radicals, allowing the reaction to proceed without the need for an exogenous chloride source.…”
Section: Resultsmentioning
confidence: 99%
“…The examination of several ligand scaffolds indicated that common bis­(oxazoline), pyridyloxazoline, and 1,2-diamine ligands ( L1 – L6 ) were ineffective for this enantioselective C­(sp 3 )–H arylation. In contrast, chiral bis­(imidazoline) ligands were found to be exceptionally effective ( L7 – L10 ). We reasoned that the increased electron-donating properties of bis­(imidazoline) ligands may facilitate the challenging oxidative addition of aryl chlorides to the nickel catalyst. Importantly, the nickel chlorides and/or aryl chlorides provide an in situ source of chlorine radicals, allowing the reaction to proceed without the need for an exogenous chloride source.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the underexplored photochemical Ni‐catalyzed enantioselective transformations could be the subject of the main focuses of synthetic chemists in the near future [90,91] . As a matter of fact, the possibility of creating optically active compounds in a stereocontrolled fashion by means of sustainable, efficient, and fully recyclable dual Ni/photocatalytic system would represent the final goal of this prominent field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Dual metal and photoredox reductive cross‐coupling reactions also represent an emerging field of development. Interestingly, stable phosphonates can be directly functionalized at the carbon adjacent to the phosphorus atom by such process [96] . Regarding phosphorus chemistry, these two approaches are still in their infancy and the next few years could see their development.…”
Section: Discussionmentioning
confidence: 99%